Analyzing Pakistan's Fragile Political, Social, and Economic Landscape: Challenges, Transitions, and Structured Solutions Needed - Abuzar Khpalwak Zazai; Najeebrahman Rahmani; Assadullah Zirak (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
Due to the increasing political, security, social, and economic challenges in Pakistan, it is necessary for everyone to have a better and more accurate understanding of it to have a clear picture of the current situation in Pakistan. The aim of highlighting the above-mentioned topics is to provide a comprehensive roadmap for identifying, analyzing, and solving issues and problems that have hindered the development and progress of the country, especially when officials are not saying much about it. This research utilizes both quantitative and qualitative methods to extract findings. Materials for the article have been gathered from electronic media, printed materials, reputable reports (UN, UNDP), etc. Based on the analysis and evaluation of the political, security, social, and economic situation of Pakistan, it can be said that country is in a precarious situation and its management is beyond the capacity of its rulers and politicians. If this situation continues, it is possible that the country's situation will become more volatile in the near future, and in that case, the possibility of Pakistan's disintegration in the coming years is conceivable.